Maximilian & the Lucha Libre Club : a bilingual lucha libre thriller - Garza, Xavier (El Paso, Texas : Cinco Puntos Press, 2016)
Max seems like any other kid until he is asked to join the Lucha Libre Club, but because of strict secrecy he cannot tell anyone of his royal wrestling blood, his uncle the king of lucha libre, The Guardian Angel.
Sequel to: Maximilian & the bingo rematch.
"A Junior Library Guild selection"--Back cover.
670
Accelerated Reader AR
Keywords: Wrestling -- Juvenile fiction; Mexican Americans -- Juvenile fiction; Families -- Texas -- Juvenile fiction; Lucha deportiva -- Novela juvenil; Mexicano-americanos -- Novela juvenil; Vida familiar -- Texas -- Novela juvenl; Suspense fiction -- Juvenile literature